ASETILASI KAYU KEMIRI (Aleurites moluccana), DURIAN (Durio zibethinus), DAN MANGGIS (Garcinia mangostana) - Febrina Heryani Tarigan; Luthfi Hakim; Rudi Hartono (Program studi Kehutanan USU, 2012)
The problem solve of unstable dimensions wood fruits and susceptible wood from termites attack was an attempt preservation of wood by acetylation. The research purposes were to knew the effect of wood variety and acetic acid concentration to retention value, to evaluated the Weight Percent Gain (WPG) and dimention stability, and to evaluated durability from attack termite based on laboratory dan grave yard test. Some kind of wood such as kemiri, durian, and manggis woods were treated by soaking during 2 weeks with acetic acid concentration of 10%, 15%, 20%, and 25%. The results showed that high retention on kemiri wood with concentration of 25% was 7.73 gr/cm3. Durian wood in concentration of 15% had WPG value (44.41%) was good dimention stability (67.8%). The increasing of acetic acid concentration caused the increasing of retention and wood resistance from termite attack in laboratory and grave yard test. Key words: acetic acid, wood acetylation, termites, WPG, ASE